Recent Advances in Fluorescent Biosensor: A Comprehensive Review - Fadhil , Zeyad; Jamil, Dalia; Salman, Huda; Hasan , Amer; Alshareef , Sohad; Kommanaboyina, Srikanth; Al-Mashhadani, Mohammed (University of Thi-Qar Journal of Science, 2024)
Herein, short review paper investigated the rapidly progress in fluorescent biosensors field and their significant influences on analytical chemistry applications. An electrical signal can be produced from a biological reaction using an integrated receptor-transducer device called a biosensor. Because there are so many uses for biosensors in the medical field, including medication delivery, environmental monitoring, water and food quality monitoring, and illness detection, biosensor design and development have become a top priority for scientists and researchers in the last ten years. In the beginning, we started to explain the basic principles of fluorescence. Then, we moved to discuss about the current advancements, creative sensor designs, and the fusion of materials science and nanotechnology. The paper highlighted the sensitivity of fluorescent biosensors by addressing a wide range of applications, including biological research, environmental monitoring, and medical diagnostics. This review paper censoriously assessed the present difficulties, such as interference and constrained dynamic range, and provided explanations into ongoing research. Advanced material and nanotechnology integration is emerging as a force that improves biosensor performance and broadens their uses. This study also discussed the future possible breakthroughs in biosensor technology and its broad use in a variety of scientific and societal fields.